Simplified Calculation Method for Overlying Pipeline Deformation Induced by Tunnel Construction in Soil Based on the Energy Principle - Minghui Yang; Tao Yang; Bo Deng (Advances in Civil Engineering)
The deformation of the overlay pipeline caused by the excavation of the soil tunnel in the case of small spacing cannot be ignored. Based on the experience of previous engineering, this paper assumes that the settlement of the overlying pipeline caused by tunnel excavation satisfies the basic morphology of Gaussian distribution. On this basis, the soil displacement is converted into load acting on the pipeline, and the energy variation principle is introduced, and the energy variation equation of the pipe-soil system is established, which is iteratively solved based on the principle of minimum potential energy, so as to obtain the calculation method of overlay pipeline vertical deformation caused by soil tunnel excavation, which is more simple and practical than the previous method. The calculation results were compared with the existing tests and engineering examples to verify the correctness of the proposed formula. Finally, the influence of pipeline material, formation loss rate, and intersection angle between the tunnel and pipeline on pipeline vertical deformation was analyzed. The comparative analysis shows that the pipeline deformation decreases with the increase of tunnel angle and pipeline elastic modulus, but increases with the increase of formation loss rate.